On the crossroads of faith: the catholic church and the Serbian Orthodox Church in the Kingdom of the Serbs, Croats and Slovenes/Yugoslavia through the eyes of US ministers and consuls in Belgrade and Zagreb - Mario Jareb (Saeculum Christianum)
Data on religious life, that is, the activities of various religious communities and organizations/churches, were often mentioned and analyzed on the pages of dispatches and reports compiled by US ministers in Belgrade and consuls in Zagreb. They are available primarily among the documents of the National Archives and Records Administration (NARA), Record Group (RG) 84, Records of Foreign Service Posts, Diplomatic Posts, Yugoslavia, and on two microfilm publications published by NARA. Most attention in dispatches and reports was devoted to the Serbian Orthodox Church as a kind of state church of the Kingdom and to the Catholic Church, which at the same time represented the vast majority of Croats (and Slovenes).